Favourable clinical outcomes following cemented arthroplasty after metal-on-metal total hip replacement: a retrospective study with a mean follow-up of 10 years - Yu, Weiguang (BMC Musculoskelet Disord, 2020)
BACKGROUND: Given the unexpected high rate of failure following metal-on-metal total hip replacement (MoM-THR), it is expected that more MoM-THR patients will experience revision. The long-term outcomes regarding the primary MoM-THR revised to cemented THR (CTHR) remain controversial. The purpose of this retrospective review was to evaluate the long-term outcomes of patients who underwent conversion from MoM-THR to CTHR. METHODS: A total of 220 patients (220 hips) who underwent a conversion of primary MoM-THR to CTHR from March 2006 to October 2016 were retrospectively reviewed. The primary outcomes were the functional outcomes assessed using the Harris hip scores (HHS) and major radiographic outcomes. Follow-ups occurred at 3 months, 6 months, 1 year, 2 years, and then every two years after revision. RESULTS: Mean follow-up was 10.1 years (5–13 years). Distinct improvements were detected in the mean HHS between the preoperative and last follow-up analysis (62.35[±8.49] vs. 84.70[±14.68], respectively, p < 0.001). The key orthopaedic complication rate was 18.2% (27/148). Seven (4.7%) cases experienced a CTHR failure at a mean of 3.4 (±1.2) years after revision MoM-THR, mostly attributed to recurrent dislocation. CONCLUSION: CTHR might yield an acceptable functional score and a low rate of the key orthopaedic complications.